1937
DOI: 10.1002/srin.193701018
|View full text |Cite
|
Sign up to set email alerts
|

Die Diffusion von Wasserstoff durch Metalle

Abstract: Bedeutung von Gefuge uOO Oberfliiche des Werkstoffes fur die Wasserstoffaufnahme von Metallen. Theorie der Wasserstoffwufnahme beim elektrolytischen Beizen. Nachweis des Oberfliicheneinflusses a1tf die Durchliissigkeit beim Gluhen. im Wasserstoff. Wasserstoffdurchliissigkeit von Mangan8tiihlen mit 0,1 bis 1,1 % G uOO 0,5 bis 4,5 % Mn bei Temperaturen bi« 850 0 und Drucken. bis 20 kg/cm 2 ) .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1951
1951
1984
1984

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…The data on ST for mild steel (5,6) indicate it is approximately 10 -' at 300~ when dQ/dt is in cc H,~ (STP)/hr, A is in cm ~, d is in ram, and P in atmospheres. Assuming a mild steel container with a wall 0.5 mm in thickness and an internal H~ pressure of 1 atm, rates of H~ effusion equivalent to a corrosion rate of 2700 mg/dm~-mo are obtained based on the reaction 3Fe + 4H~O -~ Fe~O~ § 4H~.…”
Section: Theoretical Considerationsmentioning
confidence: 97%
See 1 more Smart Citation
“…The data on ST for mild steel (5,6) indicate it is approximately 10 -' at 300~ when dQ/dt is in cc H,~ (STP)/hr, A is in cm ~, d is in ram, and P in atmospheres. Assuming a mild steel container with a wall 0.5 mm in thickness and an internal H~ pressure of 1 atm, rates of H~ effusion equivalent to a corrosion rate of 2700 mg/dm~-mo are obtained based on the reaction 3Fe + 4H~O -~ Fe~O~ § 4H~.…”
Section: Theoretical Considerationsmentioning
confidence: 97%
“…Zinc (1) and aluminum (2)(3)(4) are anodic to steel in many aqueous solutions and often corrode sacrificially to impart partial or complete protection to steel. This tendency of Zn and A1 to protect steel cathodically has been reflected in the good corrosion resistance of galvanized and aluminized steel (5), particularly in marine environments (6,7). Although cases are reported when Zn (8-10) and A1 (3,11,12) reverse their polarity with respect to steel, it is generally true, at least for the zinc-steel couple, that the chance of a polarity reversal is much decreased in the presence of chloride.…”
Section: Introductionmentioning
confidence: 99%
“…Ham and Sauter (26,28) also reported that diffusion rates of both iron and palladium were changed by the amoxmt of heating. Fuller (27) found that the penetration velocity of nascent hydrogen through iron increased upon successive electrolysis tests or acid picklings. This did not hold if there were intervening rest periods.…”
Section: F6mentioning
confidence: 99%